Recognizing and Effectively Managing Hypermobility-Related Conditions. Issue 9 (3rd June 2019) - Russek, Leslie N; Stott, Patricia; Simmonds, Jane
Abstract: Hypermobility spectrum disorder (HSD) and hypermobile Ehlers-Danlos syndrome (hEDS) can cause widespread or chronic pain, fatigue, and proprioceptive and coordination deficits resulting in functional restrictions. These conditions are common and often unrecognized, and patients are likely to present in physical therapy for musculoskeletal injuries, pain, or coordination deficits. Although physical therapy is considered central to managing these conditions, many patients report pain and iatrogenic injuries due to inappropriate interventions. The diagnostic classification for these conditions was revised in 2017 to supersede previous diagnostic categories of Joint Hypermobility Syndrome and Ehlers-Danlos Syndrome—hypermobility type/type III. It is now known that these conditions affect multiple body systems and not just joints and that patients require a holistic approach. This Perspective article will describe the 2017 diagnostic classification system, clinical presentation, examination, evaluation, and management of patients with HSD/hEDS. Both adult and pediatric cases are presented to illustrate the patient management concepts discussed. This knowledge can lead to more effective management of this patient population.